Informe de pasantía en la empresa Asinter Clomex S.A.S en el área de consultoría en comercio exterior. (2020)
The present investigation arises from the necessity before the lack of communication between the areas of the company. What needs to be defined is the information that each of the areas needs about the company so that there is a synchronization, it is necessary to increase or use different channels between areas to improve the iteration and create a corporate manual where all the information of the company can be found. company in order to increase productivity in internal communication processes to improve interaction in the areas of the company.